Peningkatan Kemampuan Pemecahan Masalah Matematika Siswa SMK melalui Problem Based Learning - Mayasari, Dian; Natsir, Irmawaty; Purwanty, Ratna (Media Pendidikan Matematika, 2025)
The implementation of teacher-focused learning cause students' mathematical problem-solving abilities is low, thus requiring more effective and innovative learning. The purpose of this study was to improve students' mathematical problem-solving abilities in vocational high schools with the Problem Based Learning model. Design method in this study used classroom action research and its implementation was two cycles, with each cycle being carried out twice face-to-face. The implementation of the study included planning, implementing actions, observation and reflection to ensure that each step received an in-depth evaluation. Data collection techniques involved direct observation, giving tests, and documenting learning activities. This study showed that there was an increase in students' mathematical problem-solving abilities. The percentage of learning completion increased from 53% to 84%. The findings of this study concluded that the implementation of the PBL model was effectively able to foster students' mathematical problem-solving abilities